2020
DOI: 10.1002/ird.2544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different amendments (organic matter and hydrogel) on the actual evapotranspiration and crop coefficient of turf grass under field conditions*

Abstract: The irrigation schedule in arid areas has to be efficient in order to reduce losses due to evaporation and deep infiltration. Irrigation optimization poses the need to establish with precision the value of actual evapotranspiration (ETa), and the crop coefficient (Kc). The water soil availability can be increased using hydrogel and organic matter amendments, and their effects could vary ETa and Kc. The aim of this study was to determine the ETa, and Kc of an experimental site with lysimeters on the Spanish Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The outcome of this calculation led to the determination of an experimental crop coefficient denoted as Kc e = 1.08. This determination was reported, for the case study, by Bandenay et al [31]. Incorporating this latest finding and adopting a crop coefficient value of Kc = Kc e = 1.08 enables the estimation of actual evapotranspiration (ETa).…”
Section: Experimental Water Balance In the Greenmentioning
confidence: 65%
See 1 more Smart Citation
“…The outcome of this calculation led to the determination of an experimental crop coefficient denoted as Kc e = 1.08. This determination was reported, for the case study, by Bandenay et al [31]. Incorporating this latest finding and adopting a crop coefficient value of Kc = Kc e = 1.08 enables the estimation of actual evapotranspiration (ETa).…”
Section: Experimental Water Balance In the Greenmentioning
confidence: 65%
“…Generally, for project or design purposes, crop evapotranspiration ETc is used, while for evaluation or real-time irrigation forecasting, actual evapotranspiration ETa is employed [35]. For this research, in the calculation of the variation in soil water storage ∆RG, the reference evapotranspiration ET 0 was used because, in this case, it was equal to the crop evapotranspiration ETc (Equation ( 3)) due to the value of Kc = kc e being equal to 1.08, which is very close to unity [31], and because ET 0PM was the value used in the experimental plot's water balance. Thus, the estimation of crop evapotranspiration for day i (ETc i ) is given by Equation ( 3), where K ci and ET 0i are, respectively, the crop coefficient for day i and the reference evapotranspiration for day i.…”
Section: Estimated Water Balance For the Greenmentioning
confidence: 99%
“…The use of hydrogel as a water retainer in the soil is a good option to optimize water use and not affect other similar grass species such as Agrostis stolonifera [38]. However, a study on oil flax showed that hydrogel application together with the seed was more effective than granular applications with traditional flax sowing machine since there was insufficient water retention where the granules were placed [39].…”
Section: Soil Moisture Contentmentioning
confidence: 99%
“…Moreover, a high bulk density value determines the compactness of the soil, hence affecting air and water movements, which could impede root growth and yield [74]. Accordingly, improving the planting medium could allow for superior gas exchange and sufficient water and nutrient supply through efficient rooting systems and mechanical support for plant growth [75,76].…”
Section: Bulk Density and Water Holding Capacitymentioning
confidence: 99%
“…The hydrogel-based method is also utilisable in vivo root phenotyping to prove the interconnected pore space filled by the nutrient-held hydrogel [76]. As WHC directly affects the percentage of pore space [73][74][75][76][77][78], the polymer could reduce irrigation requirements [25,31,73] and mitigate water limitations in particular areas. Fur-thermore, when considering fertiliser costs, adding hydrogel might be the ideal option to optimise water and nutrient employment while maintaining crop production [31,70,79].…”
Section: Bulk Density and Water Holding Capacitymentioning
confidence: 99%